Homogeneous dispersion of high-conductive reduced graphene oxide sheets for polymethylmethacrylate nanocomposites. Issue 3 (3rd March 2014) - Zeng, Xiaopeng; Yang, Jingjing; Zhang, Lizhen; Chen, Lijuan; Yuan, Wenxia
Abstract : The high cohesive interaction between reduced graphene oxide (RGO) sheets usually makes them difficult to disperse, which limits their utilization in achieving effective hybridization with polymers. We report here a new two-step route for preparing non-aggregated and high-conductive RGO powders. Graphene oxide precursor was first reduced by hydrazine hydrate in presence of a thermal unstable surfactant of cetyltrimethylammonium chloride (CTAC). Then a thermal annealing process under H2 /Ar atmosphere was further used to remove the non-conductive CTAC molecules. The prepared RGO powder exhibited an electrical conductivity of 2.23 × 10 4 S m −1 – about ten times higher than the one (N-RGO) simply reduced by hydrazine hydrate. After incorporating into polymethylmethacrylate with a 5 wt% loading, the composite showed a conductivity of 4.11 S m −1, which was 60 times as high as that of the same composite based on N-RGO powder. The addition and subsequent removal of CTAC molecules is an effective method for preparing non-aggregated and highly conductive graphene powder and obtaining good incorporation into polymer matrices.